Renoprotective effects of cinnamon oil against APAP-Induced nephrotoxicity by ameliorating oxidative stress, apoptosis and inflammation in rats - Saeed Alshahrani; Mohammad Ashafaq; Sohail Hussain; Manal Mohammed; Muhammad Sultan; Abdulmajeed M. Jali; Rahimullah Siddiqui; Fakhrul Islam (Elsevier, 2021)
Acetaminophen (APAP) is used as a primary medication in relieving moderate pain and fever. However, APAP is associated with toxic effects in renal tissue that appear because of its free radicals property. The principle goal of the present work is to assess the kidney damage by APAP and its restore antioxidative property of cinnamon oil (CO). Animals were distributed into six animals each in six groups. Rats were administered with three varying doses of CO from 50 to 200 mg/kg b.w. respectively and only a single dose of APAP. APAP induced an alteration in serum biochemical markers, imbalance in oxidative parameters, morphological changes in kidney tissue along with increased interleukins cytokines (IL-1β & 6) and caspase (3, 9) levels. CO administration significantly ameliorates all the parameters and histopathological changes were restored. Moreover, it also restored the activities of antioxidative enzymes. Our work proved that an variance of oxidative markers in the kidney by APAP is ameliorated by CO in rats. Thus, CO could be used in reducing APAP-induced nephrotoxicity.